Moral and Manners of Flappers (New Woman) in F. Scott Fitzgerald Works (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2018)
Flapper's phenomenon appeared in the 1920s in line with the feminist achievement on women's suffrage. Industrialism opened the possibility for vistas of young American generations at that time to undergo a good member of changes both in moral and manners. The characteristics of flappers are reflected in literary works by Fitzgerald, an American famous novelist. In achieving the objective of this research, a qualitative method is applied by the way of library research - collecting data from both primary and secondary sources. The former, This Side of Paradise (1919), a novel telling about the young generation, The Great Gatsby (1925) and Tender is The Night, both describing the maturity of the flappers. The outcome of the research proves that there is a similarity, in moral and manners, between the flappers in Fitzgerald's fictions and those in reality during the 1920s. The new values differed from the old ones which were maintained by the cult of true womanhood, especially in concern with those young generations performances, manners, and morals. The media encouraged the development of the new values. There is also a sense of paradox: on one hand Fitzgerald implicitly tended to spread out the moral and manners of flappers, but on the other hand, he criticizes them.